Determination of Trace Metal Levels of Cd, Pb, Cr, Ni, and Cu in Two Fish Species by STAT-MS and ICP-AES - Yaman, Mehmet; Yaman, Ibrahim H. (Atomic Spectroscopy Press Ltd, 2013)
The concentrations of five toxic metals (Cd, Pb, Cr, Ni, and Cu) were determined in two fish species, Scomber scombrus and Sparus auratus, obtained from fish markets in Turkish cities. For the determinations, slotted tube atom trap-atomic absorption spectrometry (STAT-AAS) and inductively coupled plasma atomic emission spctrometry (1CP-AES) were used. The obtained lead concentrations (mean 630 pg kg(-1)) for all Scomber scombrus samples were found to be higher than the maximum allowance concentrations (MAC) of 300 pg kg(-1). Cadmium concentrations in both fish species (mean 90 pg kg' for Scomber scombrus and 54 pg kg(-1) for Sparus auratus) were found to be around the MAC values. The mean Cr, Ni, and Cu concentrations in Scomber scombrus were 313 lig kg(-1), 280 pg and 420 pg kg(-1), respectively. The same metal levels in Sparus auratus were 324 pg 268 pg kg(-1) Cr, 323 pg Ni, and 382 pg kg(-1) Cu. Although some metal concentrations exceed the limits set by the authorities, the estimated noncarcinogenic and carcinogenic health risks by the Target Hazard Quotient and target carcinogenic risk indicate that there are no sytemic effects, and the risk of developing cancer over a human lifetime is between 2-9 in 1,000,000.
Keywords: Atomic-Absorption-Spectrometry; Iron Concentrations; Mediterranean Sea; Lead-Exposure; Copper; Cadmium; Zinc; Sensitivity; Enrichment; Chromium